Pedagogy of Slowness and Inclusive Technologies: Fostering Quality Time and Generative Communities in Hybrid Education - Cappiello, Federica (Formazione & insegnamento, 2025)
In an era marked by accelerated rhythms and increasing performance pressures, the school institution is called upon to rethink the timing, spaces, and modes of learning. This paper explores the pedagogy of slowness as a theoretical and practical perspective for building a more sustainable, authentic, and inclusive education. Within a phenomenological-existential and personalist framework, it offers a reflection on the role of digital technologies as potentially generative tools, capable of fostering educational well-being when integrated into a teaching approach oriented toward quality and the centrality of the person. The slowness-digitality pairing, often perceived as paradoxical, is here examined in terms of its concrete feasibility, within the broader vision of an integral, participatory, and relational education.